Reducing real-time traffic packet loss in mobile IPv6 using two tier buffer - M. Zaki, Salim (2008)
Mobile IPv6 is a network layer protocol for enabling mobility in IPv6 networks. MIPv6 was designed to allow nodes to be reachable and maintain ongoing connections while their location within the topology. A number of implementations of Mobile IPv6 have been done to enhance the functionality of MIPv6. This study proposes a new scheme to reduce real-time traffic packet loss in MIPv6 environment. The Network Simulator ns-2 and its extension MobiWan that supports IPv6 have been used to simulate this scheme and tested its efficiency. The scenarios in this study divided into two parts first five scenarios represent the standard Mobile IPv6 that does not support buffer, and second five scenarios with buffer. The difference between scenario and other in each part is the period of sending data from Correspondent Node to Mobile Node. However, the proposed scheme that uses buffer shows that it could reduce packet loss that occur during Mobile Node handover while the Correspondent Node sending data to Mobile Node. And this metric has been measured and compared with standard Mobile IPv6 in order to compare its efficiency. Some other metrics such as throughput and delay have been tested and compared.